Solution-Focused Counseling in Nursing Practice - Hatice Tekin; Sultan Ayaz Alkaya (Journal of Gazi University Health Sciences Institute, 2026)
The necessity of addressing an individual’s psychosocial needs in addition to their physical care in the delivery of healthcare services has made the integration of counseling approaches into nursing care a priority. Solution-focused counseling is a short-term, structured approach that focuses on an individual’s strengths, available resources, and capacity to generate solutions rather than on their problems. This review examines the literature on the fundamental principles, techniques, and application of the solution-focused counseling approach in the nursing field. Current studies indicate that this approach enhances patient motivation, supports treatment adherence, and strengthens nurse-patient communication. However, this approach has certain limitations, and it is recommended that it be used in conjunction with other methods, particularly in complex clinical situations. Consequently, it is argued that solution-focused counseling is a highly applicable, patient-centered, and empowering approach in nursing care. The purpose of this review is to explain the fundamental principles and characteristics of the solution-focused counseling approach and to evaluate its application in nursing practice.